Feed formulation, diet development and feed technology - Kaushik S.J. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
Diets should supply all the essential nutrients and energy in adequate proportions to satisfy the requirements for growth, reproduction, health and well being of the species concerned. Experimental diets with purified ingredients should be well accepted by the species concerned. For practical diets using 'least-cost' formulations, the choice and level of incorporation of the different ingredients should be based on available nutrient/energy content of each ingredient and take into account the imbalances and interactions between nutrients or ingredients, with specific attention to anti-nutritional factors (ANF). Processing techniques also affect nutrient availability and the physical characteristics of the final product such as texture, water stability or buoyancy of the diets and meet the behavioural needs of the species. Additives of technological interest should not affect nutrient availability. Success in the development of adequate aquafeeds depends on close co-operation between the feed engineer and the nutritionist.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)